Are There Food Deserts in Rainforest Cities?. Issue 4 (4th July 2017) - Davies, Gemma; Frausin, Gina; Parry, Luke
Abstract : Food deserts have been widely studied in Western contexts but rarely in transitioning economies and never within a rainforest. The Brazilian Amazon is a rapidly urbanizing region with high levels of poverty and food insecurity, providing an ideal context in which to explore this current research gap. Within this setting, five urban centers ranging from small town to metropole are examined to explore any potential variations between urban centers of different sizes and settings. A large survey was conducted with interviews in 554 food shops, assessing shop characteristics, food availability, price, and alternative household food acquisition strategies. Methods were developed to explore food deserts, accounting for food acquisition across multiple shops within a neighborhood. Insufficient access to healthy food was estimated to be widespread (42 percent of households), with access worse in smaller towns. Unlike many previous studies, local access to healthy food was not linked to neighborhood poverty and prices were generally lower in poorer areas. High levels of nonretail sourcing of food (e.g., fruit trees, fishing) in this region might lead to an overestimation of the food access problem if only retail food provision were considered. We conclude that food deserts are widespread in the rainforest cities studied, yet we highlight the importance of understanding local retail and nonretail food contexts. Finally, we question the extent to which the traditional food desert concept can be directly applied in the context of transitioning economies.